Anti-oral streptococci and anti-biofilm properties of Etlingera pavieana essential oil and its bioactive compounds proposed for an alternative herbal mouthwash - Karn Wongsariya; Jinthana Lapirattanakul; Savita Chewchinda; Pimpikar Kanchanadumkerng (My University, 2024)
Oral streptococci are the major group of bacteria in the oral cavity. Some of their species cause oral diseases that may lead to tooth loss and quality-of-life reduction, such as dental caries. One of prevention techniques to promote oral health is rinsing mouthwash after toothbrushing. This study aimed to determine the potential uses of local food, also remedy, plant in Thailand called Reaw-Horm or
Keywords: Streptococcus sobrinus; Oral microbiology and periodontitis research